Tutela judicial efectiva en procesos de alimentos que requieren conciliación como requisito de procedibilidad. Situación de Bucaramanga en el período 2012 – 2016 (2018)
This research analyzed the requirement of conciliation as procedural requirement for access to family function in the processes of food for children and adolescents, and the purpose of determining if the right of access to the administration of justice is taken into account. From a rigorous fieldwork was determined how effective the pre-judicial conciliation has been in satisfying human rights, the perceptions of those who administer justice with the faculties for the other conciliators, as well as the referrals in extrajudicial conciliation exercises and in front of the judicial demands, and even the judicial conciliations. The analysis period was from 2012 to 2016 in dependencies of the city of Bucaramanga.